2009
DOI: 10.4049/jimmunol.0804318
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Ligand Polyinosinic:Polycytidylic Acid Induces IL-17A and IL-21 Synthesis in Human Th Cells

Abstract: TLR3 and TLR9 recognize the pathogen-associated microbial patterns dsRNA and unmethylated DNA, respectively. The recent discovery that these receptors also recognize endogenous ligands from necrotic material has drawn increased attention to their involvement in autoimmunity. Th cell cytokines IL-17A and IL-21 have been assigned with pivotal roles in the regulation of such autoimmune diseases. IL-17A is the hallmark cytokine of the recently discovered proinflammatory Th cell subset TH17. By contrast, the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 64 publications
(60 reference statements)
2
28
0
Order By: Relevance
“…4). In mammal and fish, poly I:C has been widely used to mimic viral infection [28,29]. Accordingly, our data point to the different roles of grass carp RORa and RORg in immune response induced by specific pathogen-associated patterns.…”
Section: Discussionmentioning
confidence: 81%
“…4). In mammal and fish, poly I:C has been widely used to mimic viral infection [28,29]. Accordingly, our data point to the different roles of grass carp RORa and RORg in immune response induced by specific pathogen-associated patterns.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have shown that TLR3 is costimulatory for CD4 T cells (58, 59) and activation through both CD3 and TLR3 leads to expression of IL-17A, IL-21 (59), CCL3, CCL4, CCL5 and granzyme B (58). While TLR3 signaling is not sufficient to induce proliferation of T cells with anti-CD3, the addition of a TLR3 stimulus enhances CD3/CD28 costimulation-induced proliferation (58).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a new TLR3-dependent route that induces the synthesis of CD4 + T cell proinflammatory cytokines has been recently reported, extending TLR3 functions to autoimmune diseases (42). Therefore, it is possible that regulatory mechanisms described in this study can be also extended to different cell types.…”
Section: Discussionmentioning
confidence: 99%